Compósito de zeólita A magnética sintetizada a partir das cinzas volantes do carvão para adsorção de poluentes metálicos - Santos, Breno Aragão dos (2020)
The use of adsorbents from low-cost materials, such as coal fly ash, has become a target in research carried out in the field of adsorption. These residues from the coal burning industry have recycling potential aiming at the synthesis of porous materials, such as type 4A zeolites, which have a high adsorption power of metallic cations. In this study, zeolitic materials were synthesized from the fly ash of coal provided by Energia Pecém (Ceará, Brazil). The characterization of this zeolitic material and magnetic adsorbent allowed to identify the presence of two phases in the material, zeolite 4A (LTA) as the major phase and, as a secondary phase, sodalite (SOD). In the optimal conditions of adsorption proposed, the agitation speed and dosage of the adsorbent were, respectively, 200 rpm and 2.5 g L-1, while the contact time was around 20 minutes. The adsorption kinetics studies suggest the pseudo-second order model as the main mechanism that governs the adsorption speed, suggesting that the chemisorption process involved cation exchange as the predominant process. The diffusion models (Weber-Morris and Boyd) indicated the influence of external mass transfer (intra-film) as one of the limiting stages of the adsorption kinetics involved. In this way, the ion exchange process was proven by determining the concentration of Na+ ions before and after the adsorption process as a function of time. The equilibrium data of Zn2+ adsorption isotherms were governed by the Langmuir model, while the Sips model was better adjusted to the Cu2+ ion adsorption isotherm and the Redlich-Peterson model was better adjusted to the Pb2+ isotherms and Cd2+. According to the Langmuir model, the adsorption capacities for Pb2​​+, Cd2+, Zn2+ and Cu2+ were 9.28 x 10-1, 2.53 x 10-1, 8.88 x 10-1 and 1.60 mmol g-1, respectively. The comparative study for the types of linear and nonlinear Langmuir equations indicated a strong deviation in the values ​​of Qmax and KL, obtained through the coefficients (linear and angular) of the linearized equations, indicating limitation of these models in the representation of experimental data. The study of competitiveness and selectivity between the Pb2+, Cd2+, Zn2+ and Cu2+ species indicated efficient selectivity of the magnetic adsorbent only for the Pb2+ ion, on the other hand, there was a strong reduction in the adsorption capacities for all metallic cations due to the competition between them by adsorption sites of the magnetic adsorbent.